THE INFLUENCE OF CULTURE OF THE ORGANIZATION AND LEADERSHIP OF THE PERFORMANCE OF AN EMPLOYEE AT CV. LANGGENG JAYA IN BANDAR LAMPUNG - Kuswarak Kuswarak; Nuzleha Nuzleha; Yuliana Yamin; Abdillah Irwan Saputra (Universitas Sang Bumi Ruwa Jurai, 2019)
Culture is of essence implemaentasi organization who are taking and the practice of for it. Leadership was an attempt to influence others via relationship and the process of interpersonal communication to accomplish a purpose. Performance is the extent to which business organization can be achieve objectives based on the objective that went forth before. Of the multiple linear regression in a can t count of 2,681 with a significant 0,011 because probability much smaller than 0,05. Then culture organization influences employee performance. Of the multiple linear regression in a can t count of 2,379 with a significant 0,023, because probability much smaller than 0,05 so leadership influences employee performance. Of the test anova or f in be fhitung of 9,027 with a significant 0,001 because probability much smaller than 0,05 and culture organization and leadership in bersama-sama influences organisational performance. Based on research results obtained kooefisien correlation between cultural relations tehadap organization performance of 0,675 which means having huhubungan high. A correlation coefficient between leadership and employee performance of 0,644 means associate high also. And a correlation coefficient simultaneously of 0,690 which means high also. On a calculation multiple linear regression got y = 13,971 + 0,435x1 + 0,264x2 + et, it means variable x1 (culture organization) are more dominant than variable x2 (leadership) in improving the performance of an employee at CV. Langgeng Jaya.